Predictive Role of Paracentral Corneal Toricity Using Elevation Data for Treatment Zone Decentration During Orthokeratology. (2nd September 2018) - Li, Zhouyue; Cui, Dongmei; Long, Wen; Hu, Yin; He, Liying; Yang, Xiao
ABSTRACT: Purpose : To investigate the influence of paracentral corneal toricity using elevation data on the treatment zone decentration of spherical and toric orthokeratology (Ortho-k) lens. Methods : Corneal elevation difference (CED) was defined as the difference of corneal elevation between the two principle meridians at 8-mm chord, representing the paracentral corneal toricity. Seventy-five subjects included in this prospective study were divided into a low CED (LCED) group (LCED<30μm, n = 25) and a high CED (HCED) group (HCED≥30μm, n = 50). All subjects in the LCED group and 25 subjects in the HCED group (HCED I) were fitted with spherical Ortho-k; the other 25 subjects in the HCED group (HCED II) were fitted with toric Ortho-k. Corneal topography data from the right eyes were obtained at baseline and after 1 month of lens wear. The amount and direction of treatment zone decentration among the three groups were compared, and their relationships with corneal shape parameters, including central and paracentral corneal toricity, corneal asymmetry, flat-k and eccentricity, and lens diameter were analyzed using univariable and multivariate linear regression models. Results : The magnitude of treatment zone decentration was the greatest in the HCED I group ((LCED vs. HCED I vs. HCED II: 0.47 ± 0.15mm vs. 0.73 ± 0.15mm vs. 0.47 ± 0.19mm, respectively; ANOVA, p  < 0.01). Among participants fitted with spherical Ortho-k, the magnitude of treatment zone decentration was significantly correlated to paracentral CED after adjusting for the other corneal parameters and lens diameter (standard β = 0.599, p  < 0.01). No significant correlation between these parameters was found among those fitted with toric Ortho-k. Conclusions : Eyes with greater paracentral CED tend to have increased decentration of spherical Ortho-k lens, whereas toric Ortho-k appears to reduce the amount of lens decentration in eyes with CED at 8-mm chord above 30 μm.